Increased platelet activation and platelet-inflammasome engagement during chikungunya infection - Gomes de Azevedo-Quintanilha, Isaclaudia; Campos, Mariana Macedo; Teixeira Monteiro, Ana Paula; Dantas do Nascimento, Alessandra; Calheiros, Andrea Surrage; Oliveira, Douglas Mathias; Dias, Suelen Silva Gomes; Soares, Vinicius Cardoso; Santos, Julia da Cunha; Tavares, Isabel; Lopes Souza, Thiago Moreno; Hottz, Eugenio D.; et al. (Frontiers in Immunology, 2022)
Chikungunya fever is a viral disease transmitted by mosquitoes of the genus Aedes. The infection is usually symptomatic and most common symptoms are fever accompanied by joint pain and swelling. In most cases symptoms subside within a week. However, severe prolonged and disabling joint pain, that may persist for several months, even years, are reported. Although the pathogenesis of Chikungunya infection is not fully understood, the evolution to severe disease seems to be associated with the activation of immune mechanisms and the action of inflammatory mediators. Platelets are recognized as inflammatory cells with fundamental activities in the immune response, maintenance of vascular stability and pathogenicity of several inflammatory and infectious diseases. Although the involvement of platelets in the pathogenesis of viral diseases has gained attention in recent years, their activation in Chikungunya has not been explored. The aim of this study was to analyze platelet activation and the possible role of platelets in the amplification of the inflammatory response during Chikungunya infection. We prospectively included 132 patients attended at the Quinta D'Or hospital and 25 healthy volunteers during the 2016 epidemic in Rio de Janeiro, Brazil. We observed increased expression of CD62P on the surface of platelets, as well as increased plasma levels of CD62P and platelet-derived inflammatory mediators indicating that the Chikungunya infection leads to platelet activation. In addition, platelets from chikungunya patients exhibit increased expression of NLRP-3, cleaved IL-1β and caspase 4, suggestive of platelet-inflammasome engagement during chikungunya infection. In vitro experiments confirmed that the Chikungunya virus directly activates platelets. Moreover, we observed that platelet activation and soluble p-selectin at the onset of symptoms were associated with development of chronic forms of the disease. Collectively, our data suggest platelet involvement in the immune processes and inflammatory amplification triggered by the infection.